PLACE MAKING WORKSHOP BATUPASI SUB DISTRICT PALOPO CITY - Liza Utami Marzaman; Zulham A Hafid; Amiruddin Akbar Fisu; Nurhijrah Nurhijrah (To Maega : Jurnal Pengabdian Masyarakat, 2019)
The Batupasi people are the inheritors of the historical fragments of the Lalebbata area. Lalebbata is an important space in the history of Palopo City, where the economic, socio-cultural and religiosity of the Palopo people begins. This activity was carried out to try to explore the collective memory, the root of the problem and the hopes of the Batupasi residents for their increasingly 'aging' living space. The effort was outlined in a Place Making Workshop activity where Batupasi residents were invited to jointly express their dreams, hopes and imaginations in the process of being creative in shaping and rediscovering their neighborhood. This activity consists of 2 items, namely old photo exhibition, mapping and participatory planning. This process allows citizens to be able to take an impression of the past which has become their cultural values and social identity through a process of continuously defining the space which is then projected into the future so that it can continue to be felt until for the generations to come. In addition, this activity aims to identify the problems faced by Batupasi residents related to social, cultural, economic and inhabited areas.